Forest-permafrost feedbacks and glacial refugia help explain the unequal distribution of larch across continents - Schulte, Luise (Dr.); Li, Chenzhi; Lisovski, Simeon; Herzschuh, Ulrike (Prof. Dr.) (Journal of Biogeography, 2022)
Aim: The continental-scale distribution of plant functional types, such as evergreen and summergreen needle-leaf forest, is assumed to be determined by contemporary climate. However, the distribution of summergreen needle-leaf forest of larch (Larix Mill.) differs markedly between the continents, despite relatively similar climatic conditions. The reasons for these differences are little understood. Our aim is to identify potential triggers and drivers of the current distribution patterns by comparing species' bioclimatic niches, glacial refugia and postglacial recolonization patterns. Location: Northern hemisphere. Taxon: Species of the genus Larix (Mill.). Methods: We compare species distribution and dominance using species ranges and sites of dominance, as well as their occurrence on modelled permafrost extent, and active layer thickness (ALT). We compare the bioclimatic niches and calculate the niche overlap between species, using the same data in addition to modern climate data. We synthesize pollen, macrofossil and ancient DNA palaeo-evidence of past Larix occurrences of the last 60,000 years and track differences in distribution patterns through time. Results: Bioclimatic niches show large overlaps between Asian larch species and American Larix laricina. The distribution across various degrees of permafrost extent is distinctly different for Asian L. gmelinii and L. cajanderi compared to the other species, whereas the distribution on different depths of ALT is more similar among Asian and American species. Northern glacial refugia for Larix are only present in eastern Asia and Alaska. Main Conclusion: The dominance of summergreen larches in Asia, where evergreen conifers dominate most of the rest of the boreal forests, is dependent on the interaction of several factors which allows Asian L. gmelinii and L. cajanderi to dominate where these factors coincide. These factors include the early postglacial spread out of northern glacial refugia in the absence of competitors as well as a positive feedback ...